(untitled) (Medico Legal Update, 2021)
Objectives: This study was designed to explore the relationship between serum irisin hormone with Vitamin D levels and investigate the association of serum Vitamin D3 concentrations and serum irisin levels with BMI of male healthy individuals in Anbar province. Method: This study included 84 Iraqi men with the age range (20-40) year, divided into three groups depending on body mass index (BMI). The weight and height of all participants were taken to extract BMI. The ELISA method has been used to estimate levels of vitamin D and the irisin hormone in the serum. Pearson correlation coefficient was used to find the association between the studied variables. Results: The mean and standard deviation of serum vitamin D concentrations was significantly lower in all groups. This study showed there was non- significant difference in the mean of irisin among the three groups. A negative linear correlation was found between vitamin D and BMI, while a positive correlation with irisin. A positive correlation was found between irisin with BMI. Conclusion: People with a high BMI are deficient in Vitamin D. There was a positively relation between serum irisin levels and BMI.